Acupuncture and rehabilitation of the painful shoulder: study protocol of an ongoing multicentre randomised controlled clinical trial [ISRCTN28687220] - Jimenez Carmen; Godoy Ana; Gordo Isabel; Luna Francisco; Brioso Mauricio; Seminario Jose; Hernandez Luz; Fernandez Francisco; Olmo Victoria; Ortega Caridad; Medina Ivan; Madrazo Fernando; et al. (BMC, 2005)
Abstract Background Although the painful shoulder is one of the most common dysfunctions of the locomotor apparatus, and is frequently treated both at primary healthcare centres and by specialists, little evidence has been reported to support or refute the effectiveness of the treatments most commonly applied. According to the bibliography reviewed, physiotherapy, which is the most common action taken to alleviate this problem, has not yet been proven to be effective, because of the small size of sample groups and the lack of methodological rigor in the papers published on the subject. No reviews have been made to assess the effectiveness of acupuncture in treating this complaint, but in recent years controlled randomised studies have been made and these demonstrate an increasing use of acupuncture to treat pathologies of the soft tissues of the shoulder. In this study, we seek to evaluate the effectiveness of physiotherapy applied jointly with acupuncture, compared with physiotherapy applied with a TENS-placebo, in the treatment of painful shoulder caused by subacromial syndrome (rotator cuff tendinitis and subacromial bursitis). Methods/design Randomised controlled multicentre study with blind evaluation by an independent observer and blind, independent analysis. A study will be made of 465 patients referred to the rehabilitation services at participating healthcare centres, belonging to the regional public health systems of Andalusia and Murcia, these patients presenting symptoms of painful shoulder and a diagnosis of subacromial syndrome (rotator cuff tendinitis and subacromial bursitis). The patients will be randomised into two groups: 1) experimental (acupuncture + physiotherapy); 2) control (TENS-placebo + physiotherapy); the administration of rescue medication will also be allowed. The treatment period will have a duration of three weeks. The main result variable will be the change produced on Constant's Shoulder Function Assessment (SFA) Scale; as secondary variables, we will record the changes in diurnal pain intensity on a visual analogue scale (VAS), nocturnal pain intensity on the VAS, doses of non-steroid anti-inflammatory drugs (NSAIDs) taken during the study period, credibility scale for the treatment, degree of improvement perceived by the patient and degree of improvement perceived by the evaluator. A follow up examination will be made at 3, 6 and 12 months after the study period has ended. Two types of population will be considered for analysis: per protocol and per intention to treat. Discussion The discussion will take into account the limitations of the study, together with considerations such as the choice of a simple, safe method to treat this shoulder complaint, the choice of the control group, and the blinding of the patients, evaluators and those responsible for carrying out the final analysis.